2003
DOI: 10.1074/jbc.m209066200
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Glutamine-rich Region of Chick Csal1 and Csal3 Mediates Protein Interactions with Other Spalt Family Members

Abstract: Members of the spalt family of zinc finger-containing proteins have been implicated in development and disease. However, very little is known about the molecular function of spalt proteins. We have used biochemical approaches to characterize functional domains of two chick spalt homologs, csal1 and csal3. We show that csal1 and csal3 proteins repress transcription and that they can interact with each other. Furthermore, we found that truncated chick spalt proteins, similar to the truncated spalt protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 31 publications
1
68
0
1
Order By: Relevance
“…Interestingly, five additional mutations were found 3' to this region between nucleotides 1498 and 1565, but the next mutation is situated further 253 bp 3'. Based on the presumed importance of the glutamine-rich interaction domain encoded by nucleotides 687-750, which was found to mediate interaction of truncated csal1 (chick SALL1 homologue) with other csal proteins (Sweetman et al, 2003), it appears that mutations 5' of this region are also rarely detected. Taking this into account, we suggest that the mutational "hot spot region" should be refined to the region between nucleotide 764, just 3' of nucleotides 687-750 that encode the glutamine-rich interaction domain, and nucleotide 1565, 69 bp 3' of the region encoding the most aminoterminal double zinc finger domain.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, five additional mutations were found 3' to this region between nucleotides 1498 and 1565, but the next mutation is situated further 253 bp 3'. Based on the presumed importance of the glutamine-rich interaction domain encoded by nucleotides 687-750, which was found to mediate interaction of truncated csal1 (chick SALL1 homologue) with other csal proteins (Sweetman et al, 2003), it appears that mutations 5' of this region are also rarely detected. Taking this into account, we suggest that the mutational "hot spot region" should be refined to the region between nucleotide 764, just 3' of nucleotides 687-750 that encode the glutamine-rich interaction domain, and nucleotide 1565, 69 bp 3' of the region encoding the most aminoterminal double zinc finger domain.…”
Section: Resultsmentioning
confidence: 99%
“…Based on animal model data, SALL1 mutations causing Townes-Brocks syndrome were predicted to have dominant (-negative) effects (McLeskey Kiefer et al, 2003;Nishinakamura, 2003;Sweetman et al, 2003), and resulting truncated SALL1 proteins could interfere with other SALL proteins. Our results shown here prove that SALL1 is required for proper development of thumbs, ears, hearing (i. e. inner and/ or middle ear) and anus in humans, and (2) that SALL1 haploinsufficiency leads to TBS.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, these Sall1 knock-out mice did not show any phenotype in the heterozygous situation, and the homozygous mutants had only bilateral renal agenesis or severely hypoplastic kidneys with no preserved renal function (the same phenotype was observed in a knock-out mouse constructed by the authors group on two different genetic backgrounds; Kohlhase J, unpublished data). As an alternative explanation for the pathogenesis of TBS it was assumed that truncating SALL1 mutations could lead to the TBS phenotype by a dominant-negative action, with truncated proteins interfering with nuclear transport of the wild type proteins (Sweetman et al, 2003) resulting from dimerization of wild type and mutant proteins mediated by the evolutionarily highly conserved glutamine-rich domain within the aminoterminal part of all known SAL-like proteins (Buck et al, 2000;Farrell and Munsterberg, 2000;Farrell et al, 2001;Hollemann et al, 1996;Kohlhase et al, 2000;Kohlhase et al, 1999a;Kohlhase et al, 1996;Köster et al, 1997;Kühnlein et al, 1994;Onuma et al, 1999;Ott et al, 1996). McLeskey Kiefer et al created a transgenic mouse harboring a "typical" TBS-mutation within the Sall1 gene in order to mimic the molecular defect in human patients.…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory relationships between Wnt signalling and sal are also observed in Drosophila and Xenopus. Thus, wingless, a Drosophila Wnt homologue, induces sal expression during tracheal development in the fly (Chihara and Hayashi, 2000;Ribeiro et al, 2004), and TCF3 is required for Xsall2 expression in the forebrain/midbrain at the early nerula 2002; Sweetman et al, 2003;Netzer et al, 2006). First, the Nterminal part of the protein contains a 12 amino acids sequence that is able by itself to confer repression capacity and to interact with the Histone Deacetylase Complex NuRD (Kiefer et al, 2002;Lauberth and Rauchman, 2006).…”
Section: Function Of Sall Proteins In Gene Regulationmentioning
confidence: 99%
“…In particular, the Wnt, FGF, Shh, EGFR and BMP pathways participate in the activation of sall expression in different tissues and, in some cases, it has been shown that Sall proteins are key mediators of the function of these pathways during organogenesis and cell differentiation. The regulation of sal and salr in Drosophila has been studied extensively, and a number of tissue specific enhancers have been characterized Vertebrate data were collected from human, mouse, chicken and frog homologues (Bohm et al, 2007;Kiefer et al, 2002;Kiefer et al, 2003;Koshiba-Takeuchi et al, 2006;Lauberth and Rauchman, 2006;Ma et al, 2006;Netzer et al, 2001;Netzer et al, 2002;Netzer et al, 2006;Li et al, 2001;Li et al, 2004;Onai et al, 2004;Sakaki-Yumoto et al, 2006;Sato et al, 2004;Sweetman et al, 2003;Trott et al, 2001;Wu et al, 2006;Yamashita et al, 2007).…”
Section: Regulation Of Sall Gene Expressionmentioning
confidence: 99%